WARFARE AND HUMAN (IN)SECURITY IN THE HORN OF AFRICA - HERȚA, Laura M. (Studia Universitatis Babes-Bolyai Studia Europaea, 2015)
The main purpose of this article is to show that certain postulates of Realist and Neorealist thinking in International Relations (IR) are not really applicable on the regional configurations in the Horn of Africa. The main goals herein are: 1) to identify and underline certain endemic sources of insecurity in the Horn of Africa and 2) to argue that state-centric views on security in this region do not offer solutions for the security of individuals. The main argument which will be built throughout this article is that (Neo)realist, state-centric approaches do not trigger the security of states (through counter-balancing configurations and territorial gains) in the Horn of Africa and that Human Security is a more appropriate framework for analysis in this case. Basically the argument is that powerful states mean different things when exploring different regions and the huge difference between highly militarized states (hence powerful in material terms), on the one hand, and weak states, on the other, needs to be emphasized.